Linking adverbials in L2 English academic writing: L1-related differences. (November 2018) - Appel, Randy; Szeib, Andrzej
Abstract: Appropriate and effective use of linking adverbials (e.g., furthermore, in addition, on the other hand ) plays an important role in discourse cohesion, yet how these items are used by second language (L2) writers is still insufficiently understood. In the present study, a learner corpus of 150 argumentative essays was analyzed to determine how linking adverbials were used by L2 English academic writers from three different first language (L1) backgrounds (Arabic, Chinese, French). Using quantitative and qualitative measures, unique production tendencies in the writing of each L1 group were identified. Findings include relative overuse of additive linking adverbials (e.g., in addition, also ) by L1 Arabic writers, contrastive linking adverbials (e.g., however ) by L1 Chinese writers, and appositional linking adverbials (e.g., in fact, indeed ) by L1 French writers of L2 English. Pedagogical implications of these findings are discussed.